Temporal Variation of Kuroshio Nutrient Stream South of Japan. Issue 11 (6th November 2018) - Long, Yu; Zhu, Xiao‐Hua; Guo, Xinyu; Huang, Haocai
Abstract: The temporal variation of the Kuroshio nutrient stream south of Japan was examined using quarterly hydrographic data at section 137E from 2000 to 2013. During the seasonal cycle, nitrate flux and transport reach the maximum (minimum) in autumn (winter). The Kuroshio recirculation contributes about 60% to the mean eastward nitrate transport and the seasonal variations thereof. Empirical orthogonal function analysis showed two dominant modes in nitrate flux, nitrate concentration, and velocity at section 137E; these were associated with Kuroshio path meander and the Kuroshio Extension decadal oscillation. The Kuroshio large meander induced a significant increase in the eastward nitrate transport, from 609 to 1, 723 kmol/s, at the section. Due to the modulation of the Kuroshio Extension decadal oscillation, both the eastward nitrate transport and the Kuroshio recirculation were stronger in an unstable state compared to when in a stable state. The variation in the eastward nitrate transport in these dynamic patterns can be attributed to the strength, location, and spatial expansion of the Kuroshio recirculation south of Japan. Nitrate transport from the south of Japan to the Kuroshio Extension was relatively stable at 400 kmol/s. There was a strong seasonal variation in the surface chlorophyll concentration over the subtropical gyre including Kuroshio recirculation region, whereas variations in the Kuroshio region was controlled by the Kuroshio path shift. The velocity‐weighted nitrate concentration in the dense layer along the Kuroshio path increased throughout the year while that in the light layer decreased in spring and autumn and increased in summer and winter. Plain Language Summary: The Kuroshio nutrient stream induces large poleward nutrient transport in the North Pacific and has a significant impact on the low‐trophic ecosystem. Historical data suggested that the interannual variations of the Kuroshio nutrient transport south of Japan were controlled by the Kuroshio large meander and the Kuroshio Extension decadal oscillation, which depend on the strength, location, and spatial expansion of the Kuroshio recirculation gyre. However, nutrient transport from the south of Japan to the Kuroshio Extension is relatively stable, and the local surface chlorophyll concentration was also related to variations in the Kuroshio path. This study contributes to our understanding of the nutrient cycle on both the local and basin scale. Key Points: Nitrate transport from south of Japan to the Kuroshio Extension is about 400 kmol/s regardless of the flow condition Variation in eastward nutrient transport at section 137E is mainly attributed to the Kuroshio recirculation Kuroshio path meander and Kuroshio Extension decadal oscillation are dominant interannual variation patterns at section 137E